Vulgar eloquence: on the Renaissance invention of English literature - Keilen, Sean (Yale University Press, 2006)
Choosing Orpheus : the English eloquence of Whitney's Emblemes -- Shakespeare's "wild musick" -- The ancient neighborhood of Milton's Maske.